Reprodução Induzida de Lambari (Astyanax Lacustris) Utilizando Diferentes Indutores Hormonais - SANTOS, Jussara Garrido; COSTA, Deliane Cristina; TAVARES, Tainara Vieira; WANDERLEY, Alysson Martins; CAMPOS, Cristiane Meudal de; FERRAZ, André Julien (ANAIS DO ENIC, 2024)
-